Hepatitis B Vaccination Results Which dose is Sufficient for Immunosuppressive Patients? Single or Double? - Servet ÖZTÜRK; Merve KAÇAR EKER; Semra KAVAS; Onur ÇOLAK; Derya ÖZTÜRK ENGİN; Canan AĞALAR (Namık Kemal Tıp Dergisi, 2020)

(untitled)
Aim: Despite effective HBV vaccine and vaccination programs, Hepatitis B still causes nearly one million deaths annually, according to the World Health Organization. The immunization rates are high by hepatitis B vaccination especially in young healthy population. However, advanced age, comorbidities and immune deficiency affect the rates of vaccine response negatively. We aimed to evaluate the factors affecting the vaccine response in the patients who received hepatitis B vaccine in our hospital retrospectively.Materials and Methods: Patients who received hepatitis B vaccine and followed-up for immunization status were evaluated retrospectively in our vaccination unit. The patients were examined in terms of age, comorbidities, vaccine scheme, vaccine dose, utilization of immunosuppressive-biological agents, immunization success, and common characteristics of patients who did not develop immunity.Results: Anti-HBs titers were significantly lower in patients over 50 years old. In addition, lower Anti-Hbs titers were detected in patients with comorbidity and who received immunosuppressive therapy. Statistically higher Anti-HBs titers were obtained with double dose vaccination than single dose vaccination in patients receiving immunosuppressive treatment. Moreover, it was documented that a single dose vaccination protocol was applied to all seven patients who failed vaccination. Six of these patients were over 50 years old, two were diabetic, five were diagnosed with rheumatic disease and all of them were using biological agents.Conclusion: Vaccination before treatment in patients who will receive immunosuppressive therapy, administration of high dose vaccines in patients under immunosuppressive therapy or delaying immunosuppressive therapy during vaccination may be considered as appropriate alternatives. Considering the safety and cost-effectiveness of high-dose hepatitis B vaccine, it should be preferred in the immunosuppressive patient group.